2021
DOI: 10.2196/27180
|View full text |Cite
|
Sign up to set email alerts
|

The Challenge of Integrating eHealth Into Health Care: Systematic Literature Review of the Donabedian Model of Structure, Process, and Outcome

Abstract: Background Health care organizations are increasingly working with eHealth. However, the integration of eHealth into regular health care is challenging. It requires organizations to change the way they work and their structure and care processes to be adapted to ensure that eHealth supports the attainment of the desired outcomes. Objective The aims of this study are to investigate whether there are identifiable indicators in the structure, process, and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
71
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(90 citation statements)
references
References 50 publications
3
71
0
9
Order By: Relevance
“…However, according to the literature [37][38][39][40][41], some remaining constraints for the clinical applicability of digital devices have been discussed: limitations of elderly people in accessing and using technologies, need for previous digital training and caregiver support. In fact, the caregivers' deep involvement and training were essential in our study as was reported in previous research [33,34].…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…However, according to the literature [37][38][39][40][41], some remaining constraints for the clinical applicability of digital devices have been discussed: limitations of elderly people in accessing and using technologies, need for previous digital training and caregiver support. In fact, the caregivers' deep involvement and training were essential in our study as was reported in previous research [33,34].…”
Section: Discussionmentioning
confidence: 77%
“…The patients and caregivers highlighted the medical involvement with quick response to their questions. In fact, the involvement of patients, caregivers and healthcare professionals is one key point for the success of digital interactive solutions [33,34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, we are witnessing the digital transformation of medical care, with a rapid growth in eHealth, patient empowerment, and patient‐centered research 10 . Digitization is not only a tool for collecting clinical information but also a way of systematizing data collection and minimizing bias, to improve its analysis and dissemination for the benefit of patients 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Optimal sepsis care is therefore dependent on the availability of an effective health care provision system with adequate resources. Donabedian's structure-process-outcome model is a well-established approach for assessing health care quality [5], and has been applied in the elds of critical care and emergency care [6][7][8][9][10]. The sta ng characteristics of intensive care units (ICUs) can be analyzed as part of the "structure" component of Donabedian's triad.…”
Section: Introductionmentioning
confidence: 99%